2018
DOI: 10.1177/2010105818789961
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to second-hand smoke among secondary school-going adolescents: Findings from the Malaysian Adolescent Health Risk Behaviour (MyAHRB) study

Abstract: Background: Exposure to second-hand smoke (SHS) is one of the main causes of morbidity and it has been proven to be associated with an increased likelihood of smoking initiation among adolescents. Nonetheless, evidence on SHS exposure among Malaysian adolescents is scarce. Therefore, this article aims to demonstrate the magnitude and factors associated with SHS exposure among school-going adolescents in selected secondary schools in Peninsular Malaysia. Methods: Data were derived from the Malaysian Adolescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
11
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 33 publications
9
11
4
Order By: Relevance
“…Almost a quarter of Malaysian adults are smokers 14,15 , thus exposure of Malaysian adolescents to SHS is suspected to be substantial. Thus far, there have only been two studies conducted among adolescents in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost a quarter of Malaysian adults are smokers 14,15 , thus exposure of Malaysian adolescents to SHS is suspected to be substantial. Thus far, there have only been two studies conducted among adolescents in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, there have only been two studies conducted among adolescents in Malaysia. One of the studies that was conducted in Peninsular Malaysia involving 2599 students found 56.4% prevalence of SHS exposure 15 . The other study was localized in Kuala Lumpur and Negeri Sembilan and found 66.9% self-reported SHS exposure among 695 primary school students aged 12 years or younger 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to SHS was significantly higher among smokers. We postulated that SHS exposure in the parents'/guardians' car mostly originates from parents/guardians, family members or respondents who smoke, who may be more lenient towards smoking in their car and are unlikely to prohibit guests or household members, or their children, from smoking inside the vehicle 17,18,27 . No positive relationship was observed between age and exposure to SHS in parents'/guardians' cars, after adjusting for the confounding effect of other independent variables.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on SHS exposure among youth and school-going adolescents have been carried out in Malaysia 17,18 . Ghazali et al 18 reported that more than half of the secondary school-going adolescents were exposed to SHS, and the odds of exposure were higher among male, current smokers and if one of their parents/guardians smoked.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, health promotion and smoking cessation programmes that target parents/guardians who smoke can be another strategy to reduce the SHS exposure at home. The studies have shown that SHS exposure was high among youth if their parents/guardians smoke 38,39 . With knowledge, the smoking parent/guardian might be more motivated to smoke outside the house 40 ; in addition, community intervention recruiting the adults should be intensified to promote smoke-free homes and increase the smoking cessation rate, which will ultimately reduce the SHS exposure at home 41 .…”
Section: Shs Exposurementioning
confidence: 99%